Effect of salinity on seed germination and seedling growth of tomato - Ahmed, Foysal; Hossain, Md Delwar; Ullah, Md Ahsan; Rauf, Farjana Rauf; Kabir, Muhammad Humayun (Fundamental and Applied Agriculture, 2022)
The study was carried out to investigate the effects of different salt concen- trations on germination and seedling growth of four varieties of tomato. Experimental treatment included five levels of NaCl concentration (0, 25, 50, 100 and 150 mM) and four varieties of tomato (Binatomato-6, Binatomato-7, Binatomato-8, Binatomato-9). Data on germination percentage, radicle and plumule length, fresh weight of plumule and radicle, dry weight of plumule and radicle were recorded at different days after sowing (DAS) in Petri dishes. Results on main effects of varieties on germination of seed revealed that there was significant difference among four varieties of tomato at different days after sowing. At 9th days after sowing seeds, the highest percentage of seed germination (94.67%) was recorded in the variety Binatomato-6 and the lowest percentage of seed germination (61.33%) was observed in the variety Binatomato-8. NaCl solutions significantly affected seed germina- tion in tomato with the increase of NaCl solutions. At 11 days after sowing seeds, the highest percentage of seed germination (81.33%) of tomato was recorded in case of control (0 mM NaCl) and the lowest percentage of seed germination (0%) was observed in case of 150 mM NaCl salt solution. In case of combined effects of varieties and different levels of NaCl solutions on seed germination of tomato, the highest seed germination was recorded in the variety Binatomato-6 with control i.e. without any NaCl at 11 days after seed sowing. The germination percentage, germination coefficient, radicle and plumule length, seed vigor index, fresh weight of plumule and radicle, dry weight of plumule and radicle decrease with increasing NaCl salt solutions in the germination media compare to control. Result showed that among the four varieties of tomato, Binatomato-6, Binatomato-7 and Binatomato-9 are relatively more salt tolerant than Binatomato-8.